Assessing glucose and oxygen diffusion in hydrogels for the rational design of 3D stem cell scaffolds in regenerative medicine. (30th March 2018) - Figueiredo, L.; Pace, R.; D'Arros, C.; Réthoré, G.; Guicheux, J.; Le Visage, C.; Weiss, P.
Abstract: Hydrogels are attractive biomaterials for replicating cellular microenvironments, but attention needs to be given to hydrogels diffusion properties. A large body of literature shows the promise of hydrogels as 3D culture models, cell expansion systems, cell delivery vehicles, and tissue constructs. Surprisingly, literature seems to have overlooked the important effects of nutrient diffusion on the viability of hydrogel‐encapsulated cells. In this paper, we present the methods and results of an investigation into glucose and oxygen diffusion into a silated‐hydroxypropylmethylcellulose (Si‐HPMC) hydrogel. Using both an implantable glucose sensor and implantable oxygen sensor, we continuously monitored core glucose concentration and oxygen concentration at the centre of hydrogels. We demonstrated that we could tune molecular transport in Si‐HPMC hydrogel by changing the polymer concentration. Specifically, the oxygen diffusion coefficient was found to significantly decrease from 3.4 × 10 −10 to 2.4 × 10 −10 m 2 s −1 as the polymer concentration increased from 1% to 4% ( w / v ). Moreover, it was revealed during in vitro culture of cellularized hydrogels that oxygen depletion occurred before glucose depletion, suggesting oxygen diffusion is the major limiting factor for cell survival. Insight was also gained into the mechanism of action by which oxygen and glucose diffuse. Indeed, a direct correlation was found between the average polymer crosslinking node size and glucose parameters, and this correlation was not observed for oxygen. Overall, these experiments provide useful insights for the analysis of nutrient transport and gas exchange in hydrogels and for the development of future cellular microenvironments based on Si‐HPMC or similar polysaccharide hydrogels.